PEMANFAATAN DAUN MINT (Menta piperita) SEBAGAI ANTIMIKROBA ALAMI UNTUK MENGHAMBAT PERTUMBUHAN PATOGEN PADA JUS BUAH ALPUKAT - Beti Cahyaning Astuti; Eko Yuliastuti; Akhmad Mustofa; Nanik Suhartatik; Ihfan Bagas Aditya (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Previous research has identified the food safety aspects of the fresh fruit juices sold in Surakarta. The results showed that the level of microbiological contamination in fresh fruit juice was very high and it was not safe for consumption. This study aims to test the ability of mint leaves (Menta piperita) as a natural antimicrobial source to suppress the growth of pathogens in avocado juice. Mint leaves contain natural antimicrobial compounds in the form of menthol, menthone, menthophuran, and methyl acetate. The study used a factorial completely randomized design with 2 factors, namely the length of incubation time and the addition of mint leaves stored in standard room temperature and refrigerant. The incubation times were 0, 2, 4, and 6 hours. The results showed that mint leaves were able to suppress the number of Staphylococci, reaching the lowest number, namely 2.19 ± 0.00 log CFU / ml. Total Salmonella-Shigella was not detected by adding mint leaves and incubation for 6 hours at cold temperature. The total coliform count gave the final result with the lowest log colony count value in avocado juice and cold incubation temperature of 3.58 ± 0.43. The use of mint leaves as a natural antimicrobial in food is not yet effective, so it needs to be studied more about the use of its essential oil or needs to be explored for further effective methods.